Suggestion of the necessity of urban redevelopment combining cooperative planning theory and urban form characteristic analysis - Hwang Ah Sun (Lodz University of Technology Press, 2023)
Cities that have been created for thousands of years have different characteristics depending on the culture, environment, and race of each city. It is impossible to control such complex and diverse cities with a single rule or framework. Nor can there be any supreme rules for a good city. Therefore, it can be said that it is most important to clearly understand the characteristics of each city and to make a plan that emphasizes the strengths but complements the weaknesses. The ultimate goal of urban redevelopment is to improve the functions of the city, provide a better environment, and improve the quality of life of city residents. Therefore, a more practical and active approach that reflects the characteristics of the city and combines social and physical approaches is needed.
Keywords: urban morphology; governance; urban redevelopment; quality of life; Busan; Yeongdo; morfologia miast; zarządzanie; przebudowa miast; jakość życia